Perspektif Guru terhadap Perubahan Motivasi Belajar Siswa setelah Implementasi Program Makanan Bergizi Gratis di SD Kabupaten Sinjai - Putri, Marzhela M.; Haris, Hasnawi; Awaru, Andi Octamaya Tenri (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to analyze teachers’ perspectives on changes in students’ learning motivation following the implementation of the Free Nutritious Meal Program in several elementary schools in Sinjai Regency. This research uses a qualitative approach with a case study design. Data were obtained from teachers directly involved in the program. Data collection techniques included in-depth interviews, classroom observations, and documentation review consisting of program reports, academic records, and teaching–learning notes. The data were analyzed using thematic analysis, involving coding, categorization, and theme development. The findings indicate that most teachers observed an improvement in students’ motivation, particularly in concentration, active participation, and attendance. However, some students did not show significant improvement due to external factors such as family conditions and social environment. These findings highlight that the nutritious meal program positively influences student motivation, although additional support is needed to ensure equitable benefits for all learners.